Inheritance of resistance to fenoxaprop-p-ethyl in sprangletop (Leptochloa chinensisL. Nees) - Phongphitak,E. (Wiley-Blackwell, 2015)
© 2014 Weed Science Society of Japan. Sprangletop (Leptochloa chinensisL. Nees) is a serious grass weed in direct-seeded rice cropping systems in Thailand. One population of sprangletop, BLC1, was found to be resistant to fenoxaprop-p-ethyl at 62-fold the concentration of a susceptible biotype, SLC1. This study elucidated the inheritance of resistance to fenoxaprop-p-ethyl in this sprangletop BLC1 genotype. The reaction to the herbicide at 0.12-2.4mgaiL-1 was determined in the seedlings of self-pollinated resistant BLC1, susceptible SLC1 and SLC1 that had been allowed to cross-pollinate with BLC1. At 0.24mgaiL-1, all the seedlings of SLC1 were killed, while 99% of BLC1 survived, along with 5% of the cross-pollinated SLC1 seedlings, which were considered to be putative F1 hybrids. The root and shoot lengths of the F1 hybrids in 0.24mgaiL-1 of fenoxaprop-p-ethyl, relative to those in the absence of the herbicide, were close to or the same as the resistant parent, indicating that the resistance is a nearly complete to complete dominant trait. One-hundred-and-forty-one of the F2-derived F3 families were classified by their response to the herbicide at 0.24 and 0.48mgaiL-1 into 39 homozygous susceptible:72 segregating:30 homozygous resistant, fitted with a 1:2:1 ratio at χ2 = 1.21 and P = 0.56, indicating that the resistance to fenoxaprop-p-ethyl in the sprangletop BLC1 genotype is controlled by a single gene.